Addiction Severity Index Scores and Urine Drug Screens at Baseline as Predictors of Graduation From Drug Court. (November 2015) - Shah, Sanjay; DeMatteo, David; Keesler, Michael; Davis, Jennie; Heilbrun, Kirk; Festinger, David S.
Graduation rates from drug courts are impressive and are often attributed to the delivered treatments. However, it is unclear whether graduation rates are bolstered by low severity of drug use problems upon entry into drug court. To address this question, this study examined the relationship between baseline substance use severity and graduation rates among 251 drug court clients. Results revealed that participants with subthreshold drug composite scores on the Addiction Severity Index (ASI) were significantly more likely to graduate than those scoring in the mild-to-moderate or severe range. Furthermore, results revealed that participants who provided a drug-negative baseline urine were significantly more likely to graduate than those who provided a drug-positive baseline urine. A binary logistic regression analysis revealed that ASI drug composite score, urine screen, race, and years educated were statistically significant predictors of drug court graduation.